2019
DOI: 10.1007/s40195-019-00968-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleeve Plunge Depth on Interface/Mechanical Characteristics in Refill Friction Stir Spot Welded Joint

Abstract: Refill friction stir spot welding was employed to produce 6061-T6 aluminum alloy joints with different sleeve plunge depths. The interface characteristics of joint-line remnant and hook are investigated by optical and scanning electron microscopy. The joint-line remnant consists of primary bonding region and secondary bonding region, and two types of hook can be identified as downward hook and upward hook. Tensile shear results demonstrate that joint-line remnant and hook make interaction effects on tensile sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…From the figures, the hook shape that was observed for all three conditions was similar, resembling an S-shape. This behavior was expected, since the PD was kept constant during this study and, as demonstrated in the literature [ 51 ], PD is one of the main parameters in control of the hook formation and geometry. As demonstrated by Cao et al [ 42 ], this influence of the PD on the hook shape develops from the plunging stage of the shoulder, which pushes the softened material beneath it downward, squeezing the adjacent material upward.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…From the figures, the hook shape that was observed for all three conditions was similar, resembling an S-shape. This behavior was expected, since the PD was kept constant during this study and, as demonstrated in the literature [ 51 ], PD is one of the main parameters in control of the hook formation and geometry. As demonstrated by Cao et al [ 42 ], this influence of the PD on the hook shape develops from the plunging stage of the shoulder, which pushes the softened material beneath it downward, squeezing the adjacent material upward.…”
Section: Resultssupporting
confidence: 67%
“…The hook is formed due to the material flow that is promoted by the shoulder movement and its rotation during the process. According to Silva et al [ 50 ] and Sun et al [ 51 ], the observed fracture modes are often related to the shape and height of the hook. In other words, the mechanical performance of the spot is strongly related to the hook configuration.…”
Section: Resultsmentioning
confidence: 99%
“…3.1. Analysis of the RFSSW joint metallograph Figure 4(a) demonstrates a representative axial cross-sectional metallograph of the RFSSW specimen, in which zone A is the BMZ, zone B is the nugget, and zone C is the boundary zone including the heat-affected and thermomechanical affected zone [10][11][12]. 4(a) which is the metallographic measurement value of the joint's diameter, is determined to be 8.89 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The tool system consisted of an 18 mm diameter clamping ring, a 9 mm diameter sleeve, and a 5 mm diameter pin. The main welding parameters are shown in table 2, and the RFSSW process is illustrated in figure 1 [9][10][11][12]. Figure 2 shows an actual photo of the RFSSW specimen.…”
Section: Welded Materials and Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation